2020
DOI: 10.1167/jov.20.10.8
|View full text |Cite
|
Sign up to set email alerts
|

Optic flow parsing in the macaque monkey

Abstract: During self-motion, an independently moving object generates retinal motion that is the vector sum of its world-relative motion and the optic flow caused by the observer's self-motion. A hypothesized mechanism for the computation of an object's world-relative motion is flow parsing, in which the optic flow field due to self-motion is globally subtracted from the retinal flow field. This subtraction generates a bias in perceived object direction (in retinal coordinates) away from the optic flow vector at the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 74 publications
(151 reference statements)
4
26
0
Order By: Relevance
“…We have recently demonstrated flow parsing in macaque monkeys ( Peltier et al, 2020 ), including the observation that optic flow in one visual hemi-field can influence perception of object direction in the opposite hemi-field, as demonstrated previously in humans ( Warren and Rushton, 2009b ). These observations imply a global contribution to flow parsing, as might be implemented through feedback from the dorsal subdivision of the medial superior temporal area (MSTd) ( Layton and Fajen, 2016b ; Layton and Fajen, 2020 ).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…We have recently demonstrated flow parsing in macaque monkeys ( Peltier et al, 2020 ), including the observation that optic flow in one visual hemi-field can influence perception of object direction in the opposite hemi-field, as demonstrated previously in humans ( Warren and Rushton, 2009b ). These observations imply a global contribution to flow parsing, as might be implemented through feedback from the dorsal subdivision of the medial superior temporal area (MSTd) ( Layton and Fajen, 2016b ; Layton and Fajen, 2020 ).…”
Section: Discussionsupporting
confidence: 65%
“…Several studies Warren and Rushton, 2007 ; Warren and Rushton, 2008 ; Warren and Rushton, 2009a ; Warren et al, 2012 ; Foulkes et al, 2013 ; Rushton et al, 2018 have provided strong behavioral support for the flow-parsing hypothesis in humans, including some which suggest strongly that it involves a global motion process ( Warren and Rushton, 2009b ). In addition, a recent study has demonstrated flow parsing in macaque monkeys ( Peltier et al, 2020 ). If flow parsing completely discounts background motion due to self-motion, then the computations for detecting scene-relative object motion would be greatly simplified and would be essentially the same as when there is no self-motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note though, that MSTd also contains another large population of incongruent neurons with nearly opposite heading preference based on vestibular and that simulated from optic flow. It has been hypothesized that different populations of neurons in MSTd with either visuo-vestibular congruent or conflict relations could be used to segregate independent object-motion from self-motion 93 97 .…”
Section: Discussionmentioning
confidence: 99%